2022
DOI: 10.1021/acs.langmuir.2c02054
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Bright CsPbX3 Nanocrystals in Metal–Organic Frameworks for White Light-Emitting Diodes

Abstract: The stability of metal halide perovskite (CsPbX3, X = Cl, Br, and I) nanocrystals (NCs) is crucial for their practical applications. In this paper, perovskite NCs were synthesized in situ in lead-based metal–organic frameworks (Pb-MOFs: [Pb2(1,3,5-HBTC)2(H2O)4]·H2O), and we obtained stable and bright luminescence composites with different colors. Namely, CsPbBr3@Pb-MOF composites were created by the in situ growth of CsPbBr3 crystals (NCs) on Pb-MOF, which had high ion resistance, bright photoluminescence (PL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Moreover, the functional groups of Cs 3 Cu 2 Cl 5 , UiO-66-NDC, and CCL 4 /UiO were investigated by Fourier transform infrared (FT-IR) spectroscopy, and the spectra are shown in Figure c. For the pure Cs 3 Cu 2 Cl 5 NCs, the absorption peaks observed at 1636 cm –1 (N–H), 1710 cm –1 (CO), 3444 cm –1 (N–H vibrations), 1464 cm –1 (−CH 2 vibrational), and 2852 and 2926 cm –1 (asymmetric C–H stretching) are ascribed to the long-chain organic ligand, , indicating the existence of oleic acid and oleylamine on the surface of the Cs 3 Cu 2 Cl 5 NCs. Notably, all of the absorption peaks corresponding to Cs 3 Cu 2 Cl 5 NCs were also observed in the spectrum of the CCL 4 /UiO nanocomposite, and the absorption bands originating from UiO-66-NDC were clearly observed in the composites as well, further verifying the successful embedment of the NCs in the UiO-66-NDC matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the functional groups of Cs 3 Cu 2 Cl 5 , UiO-66-NDC, and CCL 4 /UiO were investigated by Fourier transform infrared (FT-IR) spectroscopy, and the spectra are shown in Figure c. For the pure Cs 3 Cu 2 Cl 5 NCs, the absorption peaks observed at 1636 cm –1 (N–H), 1710 cm –1 (CO), 3444 cm –1 (N–H vibrations), 1464 cm –1 (−CH 2 vibrational), and 2852 and 2926 cm –1 (asymmetric C–H stretching) are ascribed to the long-chain organic ligand, , indicating the existence of oleic acid and oleylamine on the surface of the Cs 3 Cu 2 Cl 5 NCs. Notably, all of the absorption peaks corresponding to Cs 3 Cu 2 Cl 5 NCs were also observed in the spectrum of the CCL 4 /UiO nanocomposite, and the absorption bands originating from UiO-66-NDC were clearly observed in the composites as well, further verifying the successful embedment of the NCs in the UiO-66-NDC matrix.…”
Section: Resultsmentioning
confidence: 99%
“…(g) XRD patterns obtained for Pb-MOFs and CsPbBr 3 @Pb-MOF. All panels are reproduced from ref . Copyright 2022 American Chemical Society.…”
Section: Cspbx3@pb-mofsmentioning
confidence: 99%
“…79 Recently, we reported on the in situ synthesis of perovskite NCs in Pb-MOFs (CsPbBr 3 @Pb-MOF composites via the in situ growth of CsPbBr 3 NCs on Pb-MOFs) to attain improved stability and brightness as well as high ion resistance. 18 Figure 3a shows a schematic illustration of the detailed preparation process. Based on our previous results, it was obvious that compared to other MOFs, the white Pb-MOF powder matrix showed great potential for providing Pb 2+ sites for the in situ growth of the CsPbBr 3 NCs and enhancing the PL density of the CsPbBr 3 @ Pb-MOF composites.…”
Section: ■ Cspbx 3 Ncs Incorporated Into Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal–organic frameworks (MOFs) have widespread applications in catalysis, gas separation, photoreduction, and other fields for their ability to control the arrangement and chemistry of the guest molecules in their pores. Preliminary studies showed that the degradation of CsPbX 3 can be noticeably slowed down by embedding the perovskite NCs inside the MOF. To further enhance the passivation efficacy, the pores of the MOF have to be sealed via a high temperature process so as to completely isolate the embedded NCs from the surroundings. However, common MOF materials like zeolitic imidazolate framework-8 (ZIF-8) usually decompose before melting when heated .…”
Section: Introductionmentioning
confidence: 99%